HUBUNGAN TASYRIâ ISLAM DENGAN UNDANG-UNDANG ROMAWI - Nurkhaerah, Sitti (Hunafa: Jurnal Studia Islamika, 2007)
Before the advent of Islam in Arab,Â  Roman Â civilization had flourished in many aspects of lives such as in philosophy, art Â and science. Even, Roma used to be a centre for Christian civilization so that it had given an influence toÂ  its neighboring lands in abovementioned aspects. However, in respect to the influence of Roman Constitution on Islamic law, a controversy emerges. Some scholars reject the influence but someÂ  support it. How the controversy emerges andÂ  what analysis employed by them to Â reject and to support Â it. This article elaborates that point.Â Â Kata Kunci: Tasyriâ Islam, Undang-Undang Romawi